Government of Nagaland Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 (Executive Summary) - Planning Commission (Planning Commission, 2002)
Nagaland joined the national mainstream of economic planning and development through the Five Year Plans only after attaining Statehood in 1963. Ever since, the State has made considerable progress in many sectors such as the Agriculture and Allied, Road communications, Power connectivity, Education, Medical, Water Supply and other Social Services sectors. However, having started almost from a scratch, despite the quantum of development and progress that have taken place in the last 38 years, the State is still deficient in many areas of basic and vital infrastructures. The State lags behind the rest of the country and continues to remain a remote and underdeveloped State of the union of India.
Planning & Co-Ordination Department Nagaland, Kohima